2016
DOI: 10.1097/md.0000000000002983
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Adductor Canal Block and Femoral Nerve Block for Postoperative Pain in Total Knee Arthroplasty

Abstract: A total knee arthroplasty (TKA) has always been associated with moderate-to-severe pain. A systematic review of randomized controlled trials (RCTs) and non-RCTs was performed to evaluate the efficacy and safety of pain control of adductor canal block (ACB) and femoral nerve block (FNB) after TKA.Relevant literatures about the ACB and FNB after TKA for reducing pain were searched from Medline (1996-January, 2015), Embase (1980-January, 2015), PubMed (1980-January, 2015), Web of Science (1980-January, 2015), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 25 publications
2
51
0
6
Order By: Relevance
“…Similarly, in a series of 100 patients undergoing anterior ligament repair, adductor canal block and femoral nerve block were found to be equal in terms of cumulative oral morphine consumption [15]. In the same way as our subjects, Dong et al [16] reported that adductor canal block (ACB) shows no superiority than femoral nerve block (FNB) group regarding muscle strength and pain control. However, Li et al [17] demonstrated that ACB preserved greater quadriceps strength more than FNB with similar pain control.…”
Section: Discussionsupporting
confidence: 57%
“…Similarly, in a series of 100 patients undergoing anterior ligament repair, adductor canal block and femoral nerve block were found to be equal in terms of cumulative oral morphine consumption [15]. In the same way as our subjects, Dong et al [16] reported that adductor canal block (ACB) shows no superiority than femoral nerve block (FNB) group regarding muscle strength and pain control. However, Li et al [17] demonstrated that ACB preserved greater quadriceps strength more than FNB with similar pain control.…”
Section: Discussionsupporting
confidence: 57%
“…This uncertainty leads to the determination of which peripheral nerve blockade to adopt by the preference of the surgeons. Two meta-analyses were published on this topic recently2122. Dong et al .…”
mentioning
confidence: 99%
“…Both FNB and ACB can give good postoperative pain relieve after TKR [33]. Recently, there has been a shifting trend from the use of FNB towards the use of adductor canal block for postoperative analgesia in patients undergoing TKA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a shifting trend from the use of FNB towards the use of adductor canal block for postoperative analgesia in patients undergoing TKA. The anterior branch of obturator nerve, the saphenous nerve, and a branch of the posterior femoral nerve within the adductor canal are sensory to the surrounding tissue of the knee joint [33,34]. Kim et al [35] femoral nerve block and adductor canal block and for post-operative pain management with TKR, they found that the comparative reduction of post-operative pain with less opioid consumption, additionally, adductor canal block had spring of the quadriceps with no difference in range of motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation